2018
DOI: 10.18632/aging.101464
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal gut microbiota composition contributes to cognitive dysfunction in SAMP8 mice

Abstract: Alzheimer’s disease is characterized by cognitive dysfunction and aging is an important predisposing factor; however, the pathological and therapeutic mechanisms are not fully understood. Recently, the role of gut microbiota in Alzheimer’s disease has received increasing attention. The cognitive function in senescence-accelerated mouse prone 8 (SAMP8) mice was significantly decreased and the Chao 1 and Shannon indices, principal coordinates analysis, and principal component analysis results were notably abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 34 publications
(40 reference statements)
3
100
1
4
Order By: Relevance
“…Furthermore, APP/PS1 mice had significantly higher alpha-diversity compared to control animals at 8 months of age in a study by Harach et al (2017). In the senescence accelerated mouse prone 8 (SAMP8) model of AD, alpha diversity was significantly lower in 7-month old SAMP8 mice as compared to age-matched controls (Zhan et al, 2018). While differences in the mouse models of AD and experimental designs might be partly responsible for these conflicting results, the true association between alpha diversity of the gut microbiome and AD still needs to be elucidated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, APP/PS1 mice had significantly higher alpha-diversity compared to control animals at 8 months of age in a study by Harach et al (2017). In the senescence accelerated mouse prone 8 (SAMP8) model of AD, alpha diversity was significantly lower in 7-month old SAMP8 mice as compared to age-matched controls (Zhan et al, 2018). While differences in the mouse models of AD and experimental designs might be partly responsible for these conflicting results, the true association between alpha diversity of the gut microbiome and AD still needs to be elucidated.…”
Section: Discussionmentioning
confidence: 97%
“…The link between AD and alterations in the gut microbiome composition has already been established in several experimental animal models (Brandscheid et al, 2017;Harach et al, 2017;Shen et al, 2017;Zhang et al, 2017;Bauerl et al, 2018;Peng et al, 2018;Zhan et al, 2018) and clinical studies (Cattaneo et al, 2017;Vogt et al, 2017;Zhuang et al, 2018). However, the exact causal mechanism is still not understood.…”
Section: Discussionmentioning
confidence: 99%
“…FMT studies in animal models ( Table 8) Zhan et al (2018) observed that wild-type mice showed decreased cognitive function after broad-spectrum antibiotic treatment. Subsequently, spatial learning and memory improved after receiving feces from senescence-resistant mice (similar to control) compared to mice receiving feces from senescenceprone mice (similar to antibiotics plus vehicle).…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 99%
“…Based on previous reports [13,15,24,25], broad-spectrum antibiotics (ampicillin 1 g/L, neomycin sulfate 1 g/L, metronidazole 1 g/L, Sigma-Aldrich Co. Ltd, St. Louis, MO, USA) dissolved in drinking water were given ad libitum to male C57BL/6 mice for 14 consecutive days (days 1-14). The drinking solution was renewed every 2 days.…”
Section: Antibiotic Cocktail Treatment Fmt and Behavioral Testsmentioning
confidence: 99%